2019
DOI: 10.1093/nar/gkz709
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic and synergistic epigenetic modulation using orthologous CRISPR/dCas9-based modular system

Abstract: Establishing causal relationship between epigenetic marks and gene transcription requires molecular tools, which can precisely modify specific genomic regions. Here, we present a modular and extensible CRISPR/dCas9-based toolbox for epigenetic editing and direct gene regulation. It features a system for expression of orthogonal dCas9 proteins fused to various effector domains and includes a multi-gRNA system for simultaneous targeting dCas9 orthologs to up to six loci. The C- and N-terminal dCas9 fusions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…They also performed a time course study after transient transfection and found that even though almost no construct was present on 8th day and the dCas9 protein was undetectable by the 11th day after transfection, the effect of DNA demethylation persisted until day 30 after transfection. Taken together with our data, these data suggest that the effect of targeted DNA demethylation by transient transfection may depend on the target genes and the TET1-dCas9 system 25 . However, DNA re-methylation over these time periods has never been reported.…”
Section: Discussionsupporting
confidence: 83%
“…They also performed a time course study after transient transfection and found that even though almost no construct was present on 8th day and the dCas9 protein was undetectable by the 11th day after transfection, the effect of DNA demethylation persisted until day 30 after transfection. Taken together with our data, these data suggest that the effect of targeted DNA demethylation by transient transfection may depend on the target genes and the TET1-dCas9 system 25 . However, DNA re-methylation over these time periods has never been reported.…”
Section: Discussionsupporting
confidence: 83%
“…Different tools have been developed in mammals to target demethylation using ZFs, TALEs and CRISPR‐dCas9 platforms (Lei et al , 2018; Josipovic et al , 2019; Taghbalout et al , 2019) (Table 1). Targeted demethylation has been achieved in plants by fusing TET1‐CD to both ZF and SunTag systems (Fig.…”
Section: Targeted Manipulation Of Dna Methylation In Plantsmentioning
confidence: 99%
“…Like synthetic transcription factors, CRs activate gene expression by recruiting transcriptional machinery to specific loci to promote or interfere with biochemical modifications. For example, fusing dCas9 with CRs such as p300, BAF, or Tet1, activates gene expression from specific loci by inducing modifications such as histone acetylation (p300) and DNA demethylation (Tet1) (Braun et al, 2017;Hilton et al, 2015;Josipovi c et al, 2019;Liu et al, 2016). Using this approach, a myogenic enhancer was selectively demethylated via transient dCas9-Tet1 recruitment enabling reprogramming of fibroblasts into myoblasts (Liu et al, 2016).…”
Section: Engineered Biochemical Systems Of Chromatin Regulationmentioning
confidence: 99%